The relationship of some Elsinoë and Sphaceloma species pathogenic on cassava and other Euphorbiaceae in Central and South America - Zeigler, Robert S.; Lozano, J.C. (Scientific Societies, 1983)
Isolates of Sphaceloma and Elsinoë spp. were collected from Euphorbia brasiliensis, Eu. heterophylla, Eu. pulcherrima, Jatropha aconitifolia var. papaya, Manihot carthaginensis, and M. esculenta in Mexico, Costa Rica, the Dominican Republic, and Colombia. M. carthaginensis and J. aconitifolia var. papaya had not been reported previously as Sphaceloma hosts, and cassava had not been previously reported as a host of Elsinoë spp. A connection between the Elsinoë from cassava with Sphaceloma manihoticola is established. Cross inoculations demonstrated that some isolates were pathogenic on several euphorbiaceous species. Pathogenicity on cassava of an isolate of Elsinoë brasiliensis from Eu. brasiliensis was enhanced by reisolation from cassava. Cultural characteristics on potato-dextrose agar were not sufficiently different to aid in separating the species. Conidial dimensions on the same medium were not significantly different among isolates from Eu. brasiliensis, M. esculenta, M. carthaginensis, and J. aconitifolia var. papaya. No significant differences were found between isolates from Eu. pulcherrima and Eu. heterophylla, but each was different from the other four. Sphaceloma krugii and S. poinsettiae both produced large, pigmented, spindle-shaped spores in addition to the more typical small, hyaline Sphaceloma conidia. In light of these studies, a combination of several species is proposed. S. poinsettiae and S. krugii are combined under S. poinsettiae, E. jatrophae, E. brasiliensis and the Elsinoë found on cassava are combined under the name Elsinoë brasiliensis.